Structural and morphological features of the ultrasound-assisted micro-arc oxidation coatings; AIP Conference Proceedings; Vol. 2167 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2019 (AMHS'19) - Kazantseva E. A. (2019, 2019)
Title screen